Mechanism and implications of comprehensive land consolidation in promoting village revitalization： Taking Dongheng Village in Deqing County, Zhejiang Province as an example - JIANG Yanfeng, LUO Danyi, ZHANG Yingnan (Ziyuan Kexue)
[Objective] Comprehensive land consolidation, as a systematic project for territorial spatial adjustment and optimization, is being widely used to alleviate rural issues and promote sustainable development of villages. The village, being the fundamental unit of rural planning and development, serves as an ideal scale to provide scientific basis for the practice of optimizing and adjusting rural territorial space. [Methods] Based on the theoretical analysis of the relationship between comprehensive land consolidation and village revitalization, this study takes Dongheng Village in Deqing County, Zhejiang Province as an example to carry out an empirical study, aiming to reveal the mechanism by which comprehensive land consolidation influences the revitalization of rural villages. [Results] (1) Under the combined influence of internal and external factors, the comprehensive land consolidation project, based on the policy system and engineering technology, drives the restructuring of rural spaces and the layout adjustment of development factors by promoting the synergistic development of different subsystems, thus contributing to village revitalization. (2) Under the joint effect of internal and external factors such as policy support, industrial foundation, resource endowment, and cooperation among rural elites, the comprehensive land consolidation project in Dongheng Village has been carried out smoothly. (3) By using comprehensive land consolidation as a platform, Dongheng Village promoted talent development, land efficiency, and industrial transformation by constructing a multi-dimensional subsystem linkage mechanism centered on governance innovation, which led to eco-friendly, intensification and high-value development of the production, living and ecological spaces, and ultimately achieved village transformation and revitalization. [Conclusion] Regions with conditions should fully utilize the role of rural elites both within and outside the administrative system and carry out comprehensive land consolidation programs tailored to local conditions, and, on this basis, promote these programs as platforms for connecting regional policies, land engineering, infrastructure construction, industrial development, and villagers’ employment. This approach can enhance their demonstrative effect and further advance rural revitalization from village level to regional level.